La lúdica en el refuerzo académico del área de Lengua y Literatura en los estudiantes de quinto año de la Unidad Educativa Ramón Barba Naranjo del cantón Latacunga provincia de Cotopaxi. - Molina Molina, Jessica Katherine (2021)
The general objective of this research was "to develop recreational activities in the academic reinforcement in the area of Language and Literature in the students of the Fifth Year of Basic General Education, of the Ramón Barba Naranjo Educational Unit of the Latacunga canton, Cotopaxi Province." The problem investigated was How to guarantee Academic Reinforcement in the Language of Literature Area? The methodology of this research will have a quantitative approach, in such a way that it allows linking quantitative data based on the problem statement, sampling, and data collection and analysis, which is used to solve the problem. Research is applied, because it seeks to make changes through the proposal. I have come to the conclusion that when applying the proposal it was evidenced that it was necessary to use recreational activities, which allow the teacher to create their own learning space, in a way that helps the student to improve their educational actions, strengthening their practices in the teaching-learning process. Therefore, it is an alternative to improve school performance in a playful and participatory way.